Structural indices of Boer, Central highland and their F1 Crossbred goats reared at Ataye farm, Ethiopia - P.N, Chiemela; B, Sandip; T.A, Mestawet; C.F, Egbu; E.H, Ugbo; E.S, Akpolu; I.J, Umanah (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study was conducted to assess the structural indices of Boer (B), Central Highland (CH) and their F1 crossbreds (CB) goats reared at Ataye farm, Amhara region. Twenty morphometric measurements and live weight (LW) were assessed on both sexes of the three genotypes totaling to 125 goats. Structural indices were calculated for the different genotypes to collaborate with the breeding objectives of Amhara Agriculture Research Institute, i.e developing meat type goats. The average values of structural indices were compared between genotypes (sex and age) while the correlation between structural indices was studied. The results of the structural indices indicated higher value for proportionality (IPr) among the CB, while weight 1 (W1), transverse pelvic index (IPT), relative body index (RBI), dactyl thoracic index (DTI), body ratio (BR) and compact index (CI) were higher for the B bucks. Among the does the values for IPr, Weight (2, 3, 4) were higher (p<0.05) among the CB and CH while IPr were similar among the B and CB. However, most of the indices showed more or less similar variation among the three genotypes. The results of the correlation for structural indices were both positively and negatively correlated among some indices. Thus, it can be concluded that the CB goats exhibit meat type traits